2008
DOI: 10.2807/ese.13.38.18985-en
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of Legionnaires’ disease linked to an industrial plant in southeast Norway, June-July 2008

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Borgen et al 83 reported on a cluster five LD cases that were linked to a biological treatment plant at a company that produced wood-based chemicals in Norway in 2008. Clinical and environmental L. pneumophila isolates showed the same sequence type (ST462).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Borgen et al 83 reported on a cluster five LD cases that were linked to a biological treatment plant at a company that produced wood-based chemicals in Norway in 2008. Clinical and environmental L. pneumophila isolates showed the same sequence type (ST462).…”
Section: ■ Resultsmentioning
confidence: 99%
“…In 23 publications, potential sources or reservoirs of Legionella were described that were only mentioned in one or two publications selected in this review. The following potential sources were considered in source investigations: discharge vessels of sullage tanks collecting bilge water from ships, a steam turbine condenser, an inoperative bedpan flusher, a steam towel warmer, an industrial air scrubber located at a WWTP (see Wastewater/Wastewater Treatment Plants), , and garden hoses. , Low LOEs (III–V) were assigned because the evidence was inconclusive or another suspected source was found to be the most likely source.…”
Section: Potential Legionella Sourcesmentioning
confidence: 99%
“…This observation is consistent with previous studies that have predicted the long-range transport of Legionella. 19,22,73 In the local climatic context of Tarbes where the decrease is slow, it seems essential that the concentration has to be already low (below 10 4 ) at 100 m from the sprinklers.…”
Section: Discussionmentioning
confidence: 99%
“…Following three major outbreaks of Legionnaire's disease in Norway in 2001Norway in , 2005Norway in , and 2008, associated with cooling towers and an air scrubber [22,23], provisions on Legionella prevention were included in Norwegian legislation, imposing on all owners of technical installations with the potential to spread Legionella to perform a risk assessment and introduce preventive measures [24]. Details are elaborated in national guidelines on the control and prevention of Legionella, identifying critical control points for risk assessments, and how to design a subsequent prevention and control programme.…”
Section: Introductionmentioning
confidence: 99%